Influence of the levels of thyroid hormones on the result of radiofrequency ablation for atrial fibrillation: literature review - Bogun, Nataliia; Brynza, Mariia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
Introduction. Atrial fibrillation is one of the most common, clinically significant cardiac arrhythmias and is associated with an increased risk of mortality, hospitalization, and deterioration in the quality of life. The prevalence of atrial fibrillation averages 1% and tends to increase with age. It is well known that aberrations of thyroid hormones have a proarrhythmogenic effect and increase the risk of cardiovascular disease. Currently, radiofrequency ablation is actively used to treat atrial fibrillation, which in most cases has high efficiency and lasting effect. However, recurrence of atrial fibrillation may occur in some patients even after radiofrequency ablation. It is known that thyroid function is closely related to the success of radiofrequency ablation and risk of relapse of atrial fibrillation after the procedure. The aim of this literature review is to determine what is already known about the effect of thyroid and thyroid-stimulating hormones levels on the outcome of radiofrequency ablation of atrial fibrillation and to analyze previous studies. Materials and methods. A complete review of the literature on atrial fibrillation and the relationship between thyroid and thyroid hormones and recurrence of atrial fibrillation after radiofrequency ablation was conducted to examine the effect of hormone levels on the success of radiofrequency ablation and recurrence of atrial fibrillation after the procedure. Results. Data from a significant number of studies suggest that the incidence of atrial fibrillation recurrence remains high after radiofrequency ablation and that thyroid hormones affect the success of radiofrequency ablation even within normal ranges. Evidence may also suggest that patients with thyroid dysfunction, even in the presence of subclinical forms, may require better monitoring of thyroid function prior to the procedure, which may reduce the incidence of atrial fibrillation recurrence. Conclusions. It should be noted that the assessment and correction of all modifying risk factors before radiofrequency ablation can prevent recurrence of supraventricular paroxysmal arrhythmias, improve the prognosis and overall quality of life in patients in this group.